2003
DOI: 10.1046/j.1365-2567.2003.01749.x
|View full text |Cite
|
Sign up to set email alerts
|

Dihomo‐γ‐linolenic acid inhibits tumour necrosis factor‐α production by human leucocytes independently of cyclooxygenase activity

Abstract: SUMMARYDietary oils (such as borage oil), which are rich in g-linolenic acid (GLA), have been shown to be bene®cial under in¯ammatory conditions. Dihomo-GLA (DGLA) is synthesized directly from GLA and forms a substrate for cyclooxygenase (COX) enzymes, resulting in the synthesis of lipid mediators (eicosanoids). In the present study, the immunomodulatory effects of DGLA were investigated and compared with those of other relevant fatty acids. Freshly isolated human peripheral blood mononuclear cells (PBMC) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 53 publications
1
30
0
Order By: Relevance
“…The findings of this study suggest that Borage Treatment with Borage oil prostaglandin increases the ratio E1/E2 by raising the availability of prostaglandin E1 via dihomogamma-linolenic acid metabolism, and its can be modulate beneficially inflammatory response due to prostaglandin with anti-thrombotic and anti-proliferative properties 7,19 . The administration of prostaglandin E1…”
Section: Inflammatory Infiltration Responsementioning
confidence: 81%
See 1 more Smart Citation
“…The findings of this study suggest that Borage Treatment with Borage oil prostaglandin increases the ratio E1/E2 by raising the availability of prostaglandin E1 via dihomogamma-linolenic acid metabolism, and its can be modulate beneficially inflammatory response due to prostaglandin with anti-thrombotic and anti-proliferative properties 7,19 . The administration of prostaglandin E1…”
Section: Inflammatory Infiltration Responsementioning
confidence: 81%
“…Dihomo-gamma-linolenic acid can modulate the inflammatory response via T-lymphocytes and monocytes, while reducing secretion of tumor necrosis factor and interleukin 1 and 2, independently of prostaglandin formation 9,19 . The findings of this study suggest that Borage Treatment with Borage oil prostaglandin increases the ratio E1/E2 by raising the availability of prostaglandin E1 via dihomogamma-linolenic acid metabolism, and its can be modulate beneficially inflammatory response due to prostaglandin with anti-thrombotic and anti-proliferative properties 7,19 .…”
Section: Inflammatory Infiltration Responsementioning
confidence: 99%
“…Recently, a C 20 PUFA with three double bonds, dihomo-␥-linolenic acid (DGLA) (20:3n-6), has attracted great interest because it has unique biological activities in addition to its importance as a precursor of a large family of anti-inflammatory eicosanoids, such as series 1 prostaglandins and thromboxanes (6,9,12,17,18,20,34,39,41,45). C 20 fatty acids such as DGLA (20:3n-6) are synthesized by sequential desaturation and elongation of dietary LA (18:2n-6) (3,14,24,33).…”
mentioning
confidence: 99%
“…We observed a significant reduction of DGLA in pPC, ePC, pSM and eSM. Experimental studies have demonstrated the anti-atherosclerotic [52], anti-inflammatory [53] and antidyskinetic [54] effects of DGLA.…”
Section: Discussionmentioning
confidence: 99%